Gender-based health interventions in the United States: An overview of the coalition for healthier community initiative. (August 2015) - Alexander, Stephanie; Walker, Elaine M.
Highlights: National data reflect that many chronic diseases disproportionately affect women. Programs that are planned and executed with gender as an integrating principle and considered to fall along a gender-equality continuum. The coalition for a healthier community promotes a community-level, public-health systems approach that is gender-based and takes into account structural barriers that impact the health of women and girls. Abstract: Health disparities by gender constitute an important yet often overlooked aspect of health around the globe. Within the United States, there is both a paucity of research as well as planned programs that take into account how socio-cultural roles and expectations for men and women may differentially affect symptoms, access to care, and treatment. Viewing women's health exclusively as a function of sex (i.e., biological) differences represents a narrow understanding that does not fully explain gaps in health disparities between men and women. In September 2010, the U.S. Department of Health and Human Services (DHHS) launched a national initiative entitled the Coalition for a Healthier Community (CHC) to employ a gender-based framework in several urban, suburban and rural communities across the nation. The Office on Women's Health (OWH) within the DHHS funded 10 coalitions to ultimately improve the health of women and girls utilizing a gender-based approach. This article provides an overview of the initiative and the focus of the special issue.